Impact of fractional power control on downlink uplink decoupled‐based HetNets in varying path loss exponent environment. Issue 7 (25th March 2022) - Ali, Sundus; Imran Aslam, Muhammad; Ahmed, Irfan
Abstract: Uplink power control in cellular networks have proved to be an effective technique for reducing uplink interference levels, resulting in improved uplink signal to interference and noise ratio, especially for cell‐edge user equipments (UEs). Having said that, the impact of fractional power control (FPC) on the performance of downlink uplink decoupled‐ (DUDe) based HetNets while considering varying path loss exponent (PLE) environment has not been investigated as of yet, the reason behind which was to simplify the system model and obtain tractable results. In this article, we have developed a generalized analytical framework, incorporating the effect of FPC, in an effort to investigate its impact on DUDe performance in varying PLE environment. Furthermore, we have considered different small base station's (SBS) transmit powers to study its effect, paired with FPC, on DUDe‐based HetNets. Moreover, we have performed a baseline comparison of DUDe performance against conventional coupled UE association based on maximum downlink received power. Performance indicators like decoupled and coupled uplink coverage probability and decoupled and coupled average spectral efficiency have been analyzed in this paper. The results presented in this paper highlight the impact of the FPC on DUDe performance in varying PLE environment. Abstract : In this paper, we have analyzed the impact of Fractional Power Control on Downlink Uplink Decoupled‐based HetNets in varying Path Loss Exponent environment. To the best of our knowledge, such an analysis of DUDe performance using stochastic geometry have not been published before. We have developed a generalized system model and derived generalized expressions for uplink network performance indicators like decoupled uplink coverage probability and average spectral efficiency. Moreover, we have performed a baseline comparison of obtained results with the ones obtained while considering coupled association criteria based on maximum downlink received signal power. We have gauged, compared and observed interesting results regarding DUDe performance under different system model parameters.